CONTENT ANALYSIS OF PROFESSIONAL TRAINING OF BORDER GUARDS IN THE REPUBLIC OF INDIA - Bhinder, Natalia (Studies in Comparative Education, 2017)
The article focuses on the content analysis of professional training of border guards in the Republic of India during basic training, professional military training, and professional military education. The author has investigated two blocks of professional training: block of obligatory courses which are studied by specialists of all border agencies as well as block of agency-specific courses and special training courses which are necessary only for border guards of particular border agency to perform their service duties that depends on peculiarities of border security in the Republic of India.Also, the article deals with the comparative analysis of the content of future officers border guards’ training at the National Academy of the State Border Guard Service of Ukraine named after Bohdan Khmelnytskyi. Having found that there are similar threats at the border in Ukraine and the Republic of India but there is a big difference between the content of professional training at Indian agency-specific educational establishments and the National Academy of the State Border Guard Service of Ukraine the author has come to the conclusion that it is important to investigate the system of professional training of border guards in the Republic of India in details especially the content of professional training with the purpose to find its strength and use it creatively in Ukraine.